2015
DOI: 10.1016/j.ijrobp.2015.07.1619
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Influencing the Utilization of Prophylactic Cranial Irradiation in Patients With Limited-Stage Small Cell Lung Cancer

Abstract: Purpose: Brain metastases are common in patients with limited-stage small cell lung cancer (LS-SCLC) due to the inability of most chemotherapeutics to penetrate the blood-brain barrier. Prophylactic cranial irradiation (PCI) is therefore recommended for use in patients with a good response to concurrent chemoradiotherapy. However, PCI is not always delivered; therefore, we investigated the reasons for PCI omission in patients who underwent therapy with curative intent. Methods and materials:We retrospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…These trials have consistently shown that PCI leads to a reduction in the incidence of brain metastases and a prolongation in survival in patients with limited disease with initial response [ 65 , 66 ]. In spite of the compelling evidence supporting the use of PCI, a recent study demonstrated that 40% of SCLC patients for whom a survival benefit from PCI has been shown, do not receive PCI due to concerns of cognitive toxicity on the part of both patient and physician [ 67 ]. A recent trial of PCI for limited-stage SCLC demonstrated a 62% (95% confidence interval 50–74%) rate of cognitive toxicity [ 68 ].…”
Section: Introductionmentioning
confidence: 99%
“…These trials have consistently shown that PCI leads to a reduction in the incidence of brain metastases and a prolongation in survival in patients with limited disease with initial response [ 65 , 66 ]. In spite of the compelling evidence supporting the use of PCI, a recent study demonstrated that 40% of SCLC patients for whom a survival benefit from PCI has been shown, do not receive PCI due to concerns of cognitive toxicity on the part of both patient and physician [ 67 ]. A recent trial of PCI for limited-stage SCLC demonstrated a 62% (95% confidence interval 50–74%) rate of cognitive toxicity [ 68 ].…”
Section: Introductionmentioning
confidence: 99%